The Effect Of Capital Expenditure On Financial Performance With Good Corporate Governance As A Moderating Variable - Made Susilawati; Parlindungan Dongoran; Tita Safitriawati; Siti Hawa; Neneng Widayati (Jurnal Teknologi dan Manajemen Industri Terapan, 2022)
This research is quantitative with an explanatory approach, namely an approach that has a fulcrum in previous research. The data used in this research is primary, which the researcher obtained from the annual report of the National Statistics Agency from 2015 to 2024. The data that the researcher obtained was analyzed using the smart PLS 4.0 analysis tool. The result in this article shows that the Capital Expenditure variable can have a positive relationship and an insignificant influence on Company Performance because the P-values are positive and below the 0.05 significance level, namely 0.063. These results are inconsistent with the second study. These results indicate no positive relationship between regional Capital Expenditure and good regional Financial Performance. Other relevant factors include Good Corporate Governance, Regional Original Income, etc. The second hypothesis in this article also shows a positive but insignificant relationship because the P-values are at 0.051, less than 0.05. Based on this, it can be concluded that this article's first and second hypotheses cannot be accepted.